Optimalisasi Model Kooperatif TAI Berpendekatan Kontekstual untuk Meningkatkan Hasil Belajar Matematika di SMA PGRI 2 Margatiga - Hanin Pujiasih (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2025)
The Team Assisted Individualization (TAI) cooperative learning model integrates individual study and group collaboration by placing students into heterogeneous teams of five to six members. Each student first learns the material independently and then brings the results to the group for discussion, synthesis, and collective responsibility. This approach is considered effective for fostering meaningful, collaborative, and efficient learning processes, particularly in mathematics education. This study aims to examine the effect of the TAI cooperative model combined with a contextual approach on students’ mathematics achievement. The research employed a quasi-experimental design conducted at SMA PGRI 2 Margatiga during the even semester. Data were collected through achievement tests that had been validated for reliability and validity. The findings indicate that the application of the TAI model with a contextual approach has a positive and significant impact on the mathematics learning outcomes of tenth-grade students. These results suggest that integrating cooperative learning with real-life contexts enhances students’ conceptual understanding and academic performance in mathematics.